2SPD-016 Biosimilars of infliximab and rituximab: does the initial strategy of selection help their prescriptions?. (March 2019) - Beyron, C; Maljean, L; Saglio, M; Leromain, AS; Jarre, C; Hellot-Guersing, M; Gadot, A; Derharoutunian, C; Roubille, R
Abstract : Background: The development of biological medicines (BM) was a major step in the treatment of chronic diseases and cancer. However, their high costs are a financial issue for hospitals. The arrival of biosimilar drugs (BD) improved their accessibilities by reducing their prices. Nevertheless, in France, their consumption is still low. Purpose: The purpose of the study was to measure and analyse the penetration rate (PR) of biosimilar Infliximab and biosimilar Rituximab in hospitals containing 300 to 700 beds in Auvergne Rhône Alpes (France). Material and methods: A web survey was sent to hospital pharmacists dispensing Infliximab and/or Rituximab to collect: consumption of Infliximab and Rituximab (biological reference products (BRM) and BD) in the first 6 months of 2018; initiation and switching strategy of BD; and education tools provided by pharmacists to patients and/or healthcare professionals. The PR was defined as the percentage of biosimilars of the total of BM. The web survey was online for 1 month. Results: Seven hospitals replied to the survey: all were consumers of Infliximab and four were consumers of Rituximab. The PR of biosimilar Infliximab was around 50% for two hospitals, around 30% for three hospitals and two hospitals did not use BD. The seven hospitals adopted the same initiation and switching strategy: biosimilar Infliximab was prescribed only for BM-naïve patients and continuous therapy could be switched with doctor's agreement. Concerning Rituximab, the PR was 100% for two hospitals, 70% for one hospital and 40% for one hospital. All four hospitals concerned reported using the same strategy: switch from the BRM to the BD for every patient. The recent introduction of Rituximab biosimilar in the French market could explain the 2 PR lower than 100%. Concerning education provided by pharmacists about BD, all had a different strategy (education to patient, to doctor, presentation in drug committee…). Conclusion: Although these hospitals adopted the same strategy of biosimilar selection, the PR were significantly different from one hospital to another. None of the education tools provided was linked to a greater biosimilar penetration. The consensus of national societies and expert recommendations should help pharmacists to convince prescribers. References and/or acknowledgements: No conflict of interest.